(untitled) (Research, Society and Development, 2021)
Brazil has high mortality rates resulting from traffic accidents, and the vast majority from motorcycle collisions. In order to understand the impact of alcohol use on traffic accidents, this study aimed to characterize the prevalence of traffic accidents caused by alcohol consumption, as well as to carry out a survey of traffic accident rates among people with levels of varied ages. This is a descriptive, documentary study with a quantitative approach carried out in a Hospital in the city of Caxias-MA, with the files of patients of different ages, who have suffered traffic accidents between the dates of August 1, 2019 and December 31, 2019. The results confirm that 457 records of traffic accidents were analyzed, among them, 165 belong to patients aged between 12 and 20 years, thus representing 36% of the total data present, in which 93 people did alcohol use, a percentage sample of 53.3% of the total, 4.2% in August, 9.7% in September, 13.9% in October, 7.8% in the month of November and 20.6% in December. It can be concluded that the use of alcohol considerably increases the rate of traffic accidents, with adolescents as the main victims, in view of some factors such as: inexperience, lack of license and recklessness.